156 Direct-To-Consumer vs. Traditional Prescriptions of PDE5 Inhibitors: A Contemporary Cost-Analysis. (1st May 2022) - Schneider, D.; Loeb, C.; el-Khatib, F.; Jenkins, L.; Yafi, F.
ABSTRACT: Introduction: After a text screen and focused telehealth visit, patients can now have access to phosphodiesterase inhibitor (PDEi) prescriptions through online direct to consumer (DTC) healthcare companies. Prescription of PDEis has unknown costs relative to the traditional office visit, especially with the availability of online discounts. Objective: This study seeks to quantify the cost of DTC PDEi treatment compared to a traditional physician visit and local pharmacy prescription. Methods: Nine pharmacies were included, including two DTC companies, two compounding pharmacies with national reach, three online Canadian pharmacies licensed by the Canadian International Pharmacy Association, and sixteen American pharmacy chains, representing all locally available chains. National pharmacies which are subsidiaries were grouped together. Prices for chains were determined using their publicly available price on GoodRx® with coupons in Irvine, CA (92612), Cleveland, OH (44101), New York, NY (10001), Dallas, TX (75201), and Birmingham, AL (35201). Cost of physician visit was determined using 2020 CMS reimbursement for a level 3 new patient visit. Prices for DTC companies were acquired from direct communication with the company. Where offerings did not align with 90 dose regimens, price per pill was determined and price for 90 doses was calculated. Results: For a 90-dose supply of sildenafil 20mg, a physician visit and local prescription cost a mean of 191.51 with a low of 125.45, compounding pharmacy prescription cost a mean of 218.28 with a low of 144.35, and Canadian pharmacy prescription cost a mean of 240.25 with a low of 169.34, compared to a mean of 220.00 and a low of 180.00 for online DTC. For sildenafil 100mg, a physician visit and local prescription had a mean cost of 524.11 with a low cost of 137.16, compounding pharmacy prescription a mean cost of 401.78 with a low cost of 289.35, and Canadian pharmacy prescription a mean cost of 262.63 with a low cost of 200.36, compared to a mean and low cost of 900.00 for DTC. For tadalafil 5mg, a physician visit and local prescription cost a mean of 205.79 with a low of 125.80, compounding pharmacy prescription cost a mean of 179.33 with a low of 169.35, and "Canadian" pharmacy prescription cost a mean of 207.59 with a low of 195.34, compared to an average and low of 720.00 for DTC. Finally, for tadalafil 20mg, a physician visit and local prescription cost a mean of 643.70 with a low of 161.00, compounding pharmacy prescription cost a mean of 359.33 with a low of 289.35, and Canadian pharmacy prescription cost a mean of 291.74 with a low of 229.00, compared to a mean of 3420.00 and a low of 2880.00 for DTC (Table 1). Conclusions: Our findings suggest that local pharmacies, in conjunction with online coupons, provide a markedly less expensive option for fulfillment of PDEi prescriptions than online DTC services, compounding, or Canadian pharmacies, along with the established benefits of physician visits for screening. This is most pronounced if patients have flexibility in where they fill their prescriptions and can use the available local prices. Disclosure: Work supported by industry: no. A consultant, employee (part time or full time) or shareholder is among the authors (FY: Coloplast (consultant), Cynosure (consultant) LJ: Hims (consultant)).